Persisting inequalities: Women in social policies (Argentine 2000 – 2010) - Anzorena, Claudia (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The relationship between women and the State is complex. Since they were incorporated into social planning during Peron’s regime up to the current strategy of social unemployment intervention, this relationship has been changing. However, there is a constant theme underpinning them: expectations for survival and care of dependent persons are placed on women. Analyzing the complex role that women play in social policies contributes to the debate about the relations among the State, the market and civil society -a set of relationships that structures the capitalist system and its interconnections with gender inequality. Being a woman or a man is not just a quality: bodily differences are deeply intertwined with social processes.